Culture and organizational structure of businesses in san isidro to boost local tourism - Villacis Zambrano, Lilia Moncerrate; Zambrano-Vera, Eura María; Ormaza Esmeraldas, Elizabeth Del Carmen; Ferrin Delgado, Estrella Gloria Antonia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The work investigated was to analyze how the organizational culture of the well-organized businesses of San Isidro can boost local tourism, building a reference framework that allows acquiring knowledge of the organizational structure in communal shops, to facilitate the order and division of them activities of the community sector and thus having a reliable organization for the community. for it to be used the quantitative, qualitative methods, together with the method of experts, if the technique of the survey was used, the results were tabulated in the ESPSS 27, which allowed to draw the reliability of 0,89 seconds in the alpha of Cronbach alpha. One of the most preponderant elements that were found in research was essential for organizational culture, being in line with the structure, because it is the basis of a joint society to carry out a common good of any type of personal or group business, bearing in mind that this is the main part for the execution of the activities designated in the same, the organized trades are supplying the local visiting tourists and foreigners formed by entities that inhabit the locality are acquired as a point of knowledge of the various capacities, if seen expendable that the merchants receive organization workshops and a formalization of the structure of their business, only then will satisfy the visitors within the Parroquia San Isidro.